Projeto conceitual e sistema de controle de VANT penta-rotor para aplicações agrícolas - Rosa, Lucas Wilke Dalla (2020)
This work deals with the design of an penta-rotor Unmanned Aerial Vehicle (UAV), covering the conceptual phase, control project and simulations that allows validating the operation of the complete system. Such a vehicle is intended for use in agricultural applications, spraying crops or similar applications. For this, a penta rotor type vehicle with coaxial central engine and combustion propulsion is proposed. The work covers the conceptual design in CAD, based on research on propulsion, payload required and products available in the market. With the CAD defined, the mathematical modeling of the aircraft is carried out, taking into account its mass, inertia and center of gravity variation, which are of fundamental importance in this work. After the modeling is finished, it is started the design of the optimal control system with reference tracking, where the reference is generated by a guiding algorithm. The design of the UAV discrete control system is also done in this work, being implemented in an embedded microcontroller for Hardware In The Loop testing. The software used in the design of the controllers is MATLAB/Simulink and the microcontroller is the Arduino Uno.